(untitled) (Journal of the College of Basic Education, 2023)
Abstract: This paper will find the approximate solution to the linear and nonlinear fuzzy boundary value problems using the variational iteration method. The numerical scheme is based on analyzing the fuzzy problem into two crisp sub-problems. The first is for the upper solution and the second is for the lower solution of the fuzzy solution. Also, the convergence of the obtained variational iteration formula has been proved to converge to the exact solution of the problem under consideration in each illustrative example, since there is no general formula that may be obtained for the correction functional related to the problem under consideration which is due to the variation of the general Lagrange multiplier from one problem to another. Keywords:Fuzzy boundary value problems, variational iteration method, solution of fuzzy differential equations using variational iteration method.